mediação cultural na escola: possibilidades de fazeres docentes a partir de linguagens da arte no contexto de pandemia covid-19 - Sousa, Lutrícia Hiani Machado Monti (2021)
This research intends to analyze how the cultural mediation can contribute to the cultural formation of teachers and students of the Basic Brazilian Education. It assumes that how wider the repertoire and the cultural access of the mediator is there will be greater appropriation of cultural expressions at the scholar classes. The objective of the following research is to investigate what the state of art presents about the theme in order to identify the cultural expressions produced due to the context of the covid-19 pandemic. The corpus of the research is some dissertations and thesis of the Capes catalogue published in the last three years. In reference of the cultural products, they were searched in virtual platforms filtrated by the following subjects: Literature, Visual Arts and furthermore arts languages. The theoretical reference covers some contributions of Adorno & Horkheimer (1985), in matter of discussions about the Cultural Industry, Barbosa (2010) in matter of Art and Education and the triangular approach, Martins (2018; 2012) and Vygotsky (1991) on cultural and professor mediation and the interlacement between subjects and school. The results show that the cultural formation of teachers is still a great challenge in the educational real process because of its lack of accessibility. However, the teacher as a cultural mediator can propose educative ways in dialogue with the socially built cultural expressions. In addition, the cultural production at the pandemic time shows potentials pedagogic uses, once that technology can promote cultural access contributing with cultural repertoire and aesthetics experiences of the teacher. The product of this research is an didactic guide for teachers in order to bring them possibilities of expanding their cultural formation besides promoting new cultural access from the arts languages released in the covid-19 pandemic.